2022
DOI: 10.1002/puh2.7
|View full text |Cite
|
Sign up to set email alerts
|

Can Thailand achieve COVID‐19 herd immunity?

Abstract: The COVID‐19 outbreak has had a great impact on the social, economic, and health systems of Thailand. A variety of measures to curb the spread of the disease were implemented since the beginning of the pandemic, including a strict national lockdown protocol. The Thai government aimed to achieve herd immunity through an efficient vaccination programme. Initially, vaccine supply shortage and a lack of vaccine options plagued the health system, but this has since been improved. Continuous monitoring of the situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…There are seven vaccine types used in Thailand: Moderna, Pfizer, Johnson & Johnson, AstraZeneca, Sinopharm, Sinovac, and Serum Institute of India [1,12]. These vaccines have different storage and transportation requirements, with several vaccines needing ultracold storage (e.g., −80 • C for Pfizer).…”
Section: Cold Chain Logisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are seven vaccine types used in Thailand: Moderna, Pfizer, Johnson & Johnson, AstraZeneca, Sinopharm, Sinovac, and Serum Institute of India [1,12]. These vaccines have different storage and transportation requirements, with several vaccines needing ultracold storage (e.g., −80 • C for Pfizer).…”
Section: Cold Chain Logisticsmentioning
confidence: 99%
“…COVID‐19 is a global public health threat that has overburdened the health‐care systems across countries. To attain herd immunity, vaccination programs have been conducted globally since 2021 [1]. However, COVID‐19 vaccine wastage continues to hamper this progress: Publicly available reports showed that approximately 158 million doses have been discarded as of July 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontline healthcare workers (HCWs), people with underlying chronic conditions, and people aged ≥60 years were prioritized target populations for vaccination [ 5 ]. Given the high number of COVID-19 cases in Bangkok, the capital city of Thailand, it was classified as a red zone and considered a top priority for vaccination [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frontline healthcare workers (HCWs), people with underlying chronic conditions, and people aged ≥ 60 years were prioritized target populations for vaccination [5]. Given the high COVID-19 cases in Bangkok, the capital city of Thailand, it was classi ed in a red zone and considered a top priority for vaccination [6,7].…”
Section: Introductionmentioning
confidence: 99%